Pengaruh Permainan Tradisional Engklek terhadap Perkembangan Kecerdasan Kinestetik Anak Kelompok B di TK Alkhairat Tatura: The Influence of the Traditional Engklek Game on the Development of Kinesthetic Intelligence in Group B Children at Alkhairat Tatura Kindergarten - Alhaddad, Nursyafi'ah; Amrullah; Hesti Putri Setianingsih (Indonesian Journal of Early Childhood: Jurnal Dunia Anak Usia Dini, 2025)
This research is meant to examine the impact of the engklek traditional game in developing the kinesthetic intelligence of 5–6-year-old children in group B at TK Alkhairaat Tatura. Kinesthetic intelligence is the capacity to effectively use body movements to convey thoughts or ideas, solve problems, and coordinate physical movements such as strength, agility, and balance. This ability is essential to nurture during early childhood as it supports the development of gross motor skills and active engagement in the learning process. Quantitative method with pre-experimental design (one group pretest-posttest) was utilized. The sample included 10 children whose physical abilities were assessed before or after engaging in the engklek game activity. Data were collected through interviews, observations, and documentation, and subsequently analyses were conducted using descriptive and inferential methods, including signed rank-test. The findings showed a significant improvement in children's kinesthetic intelligence after the intervention. The Wilcoxon test results with a statistical value of Z were -2.972 with a significance level of 0.003 < (0.05), indicating a significant difference between before and after treatment. The aspects that improved include leg strength (jumping on one foot), body agility (zigzag running), and balance (walking on a balance beam). In conclusion, the traditional game of engklek positively influences the development of kinesthetic intelligence. This game can serve as an enjoyable and effective learning strategy for enhancing children's physical-motor skills in early childhood education settings.   ABSTRAK  Studi ini dimaksudkan guna mengidentifikasi pengaruh permainan tradisional engklek pada perkembangan kecerdasan kinestetik anak berusia 5–6 tahun di kelompok B TK Alkhairaat Tatura. Kecerdasan kinestetik ialah keterampilan dalam memanfaatkan bagian tubuh secara terampil dalam rangka mengungkapkan gagasan, menyelesaikan masalah, serta mengoordinasikan gerakan fisik seperti kekuatan, kelincahan, dan keseimbangan. Kecerdasan ini penting dikembangkan sejak usia dini karena mendukung pertumbuhan motorik kasar anak dan keterlibatan aktif dalam proses belajar. Pendekatan kuantitatif berdesain pra-eksperimental (one group pretest-posttest) dimanfaatkan. Sampel mencakup 10 anak yang diamati kemampuan fisiknya sebelum dan sesudah mengikuti kegiatan permainan engklek. Data dikumpulkan dengan teknik wawancara, observasi, serta dokumentasi, yang selanjutnya dianalisis secara deskriptif serta inferensial menggunakan uji wilcoxon. Temuan ini memperlihatkan adanya peningkatan signifikan pada kecerdasan kinestetik anak setelah diberikan perlakuan. Hasil uji wilcoxon dengan nilai statistik Z sebesar -2.972 dengan taraf Sig. 0.003 < (0.05), maka diidentifikasi perbedaan signifikan antara sebelum maupun setelah perlakuan. Aspek-aspek yang mengalami peningkatan meliputi kekuatan kaki (melompat satu kaki), kelincahan tubuh (lari zigzag), dan keseimbangan (berjalan di atas papan titian). Kesimpulannya, permainan tradisional engklek memengaruhi perkembangan kecerdasan kinestetik secara positif. Permainan ini mampu menjadi sebagai strategi pembelajaran yang menyenangkan serta efektif dalam menghasilkan peningkatan kemampuan fisik-motorik anak di lingkungan pendidikan anak berusia dini.